Fanaticisn And Zealots Khattbiya As A Model (Journal of the College of Basic Education, 2022)
The phenomenon of hyperbole represented in Arab and Islamic history is one of the important phenomena that have emerged in Muslim societies since early, this phenomenon has had a wide resonance and a strong response among the societies (new to Islam) - although it was adopted by the Arabs themselves ... like the proletariat in the adoption of this phenomenon and dealing with it as a religion approved by religion... These ideas were "hyperbole", clear reactions in the midst of internal conflicts that were evident in Arab and Islamic societies; Such as the Hashemite-Umayyad conflict is a great scourge of the party and the conflict that took place in the context of the sectarian conflict which was achieved through the phenomenon of hyperbole and its framing of the framework of human dignity and immortality. The Alawi-Abbasi conflict added more space to the phenomenon of hyperbole ... This is illustrated by the large movements of hyperbole and the wide range of intellectual mutants from small groups to teams of meaning and building and a visible role in the many horrors and revolutions that were issued in the name of these teams of hyperbole ... Perhaps the centrality and firmness that the cruelty and strength represented during the period of the Umayyad rule (41 AH. - 132 AH.) is what gnawed at the back of these movements and prevented them from appearing in public and at least wide. However, the success of the Abbasid revolution against the Umayyads by calling them "Al-Redah from the family of the house" and the real exposure towards the Abbasid state contributed in one way or another to the expansion of the activities of the hyperbole groups ...Hyperbole began Al-Sabaayah that branched out of which Hyperbole teams begin to political extremism, which like the Al - Khawarij Group, Then in ideological Hyperbole Who started with Kisaniyah and from there he dragged him ...So that resulted from these Hyperbole teams ... played group a serious role in societies through its development of the ideas of the Hyperbole and its emphasis on interpretation and solace ... The rhetorical group of the most active precious teams that have emerged, including groups and teams have been present and active communities, It was able to graduate from the establishment stage to the industry of countries... The rhetorical group it has been divided into: hyperbole, group of Al-Mokhmsah, The band is mystical and Ismayliya group... And other descriptions that accurately reflect their activity and move in regions and cities in a manner (pragmatism), If it is true verbal expression ... Islamic Thought and did not get rid of Plankton hyperbole ideas that I took her by the beliefs of many teams and groups present even today...